Impact of instructional intervention program upon women's psychological health status who undergo chemotherapy after mastectomy - Ibrahim, nuha; ali, Rabia (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): To determine the impact of instructional intervention program upon psychological health status forwomen who undergo chemotherapy after mastectomyMethodology: The sample consisted of (100) women, (50) considered as study group, and another (50) the controlgroup. A pre test was done for both groups (study and control), and then the study samples were exposed to aninstructional intervention and three-dimensional post tests and the length of time between each test 21 days inthe Institute and Hospital of Radiation and Nuclear Medicine. The questionnaire composed of three parts, first,demographic information; include (age, educational level, type of family, occupation, marital status, and adequacyof monthly income). Second, information about breast cancer include (the period in which the disease wasdiagnosed, the type of breast cancer, method of chemotherapy administration, the period of the chemotherapy,the order of the current session of chemotherapy treatment, the number of chemotherapy sessions, the source ofinformation of chemotherapy side effects. Information on previous medical history and consists of (the previousproblem of the breast, the type of injury, the site of disease, type of surgery, stage of the cancer when it wasdiscovered, family members who suffer from breast cancer). Third, the psychological effects. Pre and post test wasused to determine the reliability of the questionnaire with a time interval for a period of more than 3 weeksbetween each test, the results (r = 0.9013) for the psychological effects. Analysis of data was performed throughthe application of descriptive and inferential statistical data analysis approach.Results: Revealed that there is lack of information in women treated with chemotherapy after mastectomy beforethe implementation of the program regarding the side effects of chemotherapy treatment, and the symptomswhich appear on patients increase their anxiety and negative psychological symptoms but after theimplementation of the program the information of women become well and their psychological status improved.Recommendations: the study recommended that the Institute and Hospital of Radiation and Nuclear Medicinemust include an instructional intervention program concerning the psychological health of women who are treatedwith chemotherapy after mastectomy